Percepção de idosos sobre barreiras e facilitadores ambientais e sua relação com quedas - Donato, Ana Paula (2021)
Falls have an important negative impact on the lives of the elderly, since this event may compromise their physical, emotional and social health. Among the factors that contribute to the occurrence of this event, there are those of an intrinsic nature, linked to physical, cognitive and behavioral changes and extrinsic nature, such as the environment. Thus, the objective of the present research was to investigate and relate the environment perception with fear, risk and number of falls in the elderly. This is an epidemiological, descriptive, cross-sectional study with a quantitative / qualitative approach, which included subjects aged 60 years or older, residents of three neighborhoods in the urban area of the city of Santa Maria-RS, selected according to income and percentile of elderly people for the total population. Subjects who presented cognitive decline, lived in Long Term Care Institutions for the Elderly, or were unable to move were excluded from the study. The approach was carried out with a home visit, using as data collection instruments, an evaluation form with sociodemographic and health issues, the Timed Up and Go (TUG) test, a questionnaire containing the International Falls Efficacy Scale-Brazil (FES-I-Brazil) in order to assess the risk and fear of falling and the Activity-specific Balance Effectiveness Scale (CEA), in order to identify confidence in balance. The subjects were also invited to take a short walk near their residence in order to identify barriers and facilitators for falls, using the Stanford Discovery Tool application. The collected data were described and analyzed using the SPSS version 20.0. The Kolgomorov- Smirnov normality test and the Pearson correlation test were performed to analyze the relationship between the variables. The level of significance was set at 5%. The answers obtained by the Discovery Tool app were analyzed qualitatively, by categorization. It was observed that the elderly had, on average, less than one fall in the prior year, mild concern or fear of falling, low risk of falls and good perception of their balance. Regarding the total number of barriers, 54.8% of them perceived two barriers and 54.8% perceived no facilitator. The highest frequency of perceived barriers was observed in the neighborhood of high socioeconomic level, with emphasis on irregular / poorly maintained sidewalks. Among the facilitators, a higher frequency was also observed in this neighborhood, with emphasis on the preserved public sidewalks. It was concluded that the environment perception was not related to the variables fear, risk and number of falls.